Art Deco and Soviet Architecture - Nikolai Vasiliev (Проект Байкал, 2019)
The article tries to reveal the peculiar features of architecture of the USSR in the 1930s as a Soviet version of the world-wide Art Deco stylistics. It primarily considers the role of formal categories relating to architecture of the interwar period, and, first of all, the category of tectonics.